2010
DOI: 10.1097/bcr.0b013e3181d0f549
|View full text |Cite
|
Sign up to set email alerts
|

Obesity: Influence on Length of Hospital Stay for the Pediatric Burn Patient

Abstract: Childhood obesity is a major public health problem in the United States and is associated with numerous comorbidities. The relationship of obesity to risk of traumatic injury and recovery has been described, although not in depth. In adults with burns, obesity has been linked to negative impact on functional outcomes as well as increased mortality. Less is known about the impact of obesity on children with burns. The primary objective of this study was to determine the effect of obesity on length of hospital s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 30 publications
1
28
0
1
Order By: Relevance
“…[1][2][3] Recent studies have demonstrated worsened pediatric in-hospital outcomes, including mortality and increased resource utilization, for children with obesity across a range of diagnoses. [4][5][6][7][8][9][10] Although the mechanisms driving the association between obesity and in-hospital outcomes are not fully known, for asthma it is believed that adipocytes expressing inflammatory markers create a low level of systemic inflammation, thereby increasing the severity of allergic-type illnesses and decreasing the response to anti-inflammatory medications, such as steroids. [11][12][13][14][15][16][17][18] The relationship of obesity and in-hospital asthma outcomes is of particular interest because status asthmaticus is the most common reason for admission in children aged 3 to 12 years, accounting for approximately 150,000 admissions (7.4% of all hospitalizations for children and adolescents) and $835 million in hospital costs annually.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Recent studies have demonstrated worsened pediatric in-hospital outcomes, including mortality and increased resource utilization, for children with obesity across a range of diagnoses. [4][5][6][7][8][9][10] Although the mechanisms driving the association between obesity and in-hospital outcomes are not fully known, for asthma it is believed that adipocytes expressing inflammatory markers create a low level of systemic inflammation, thereby increasing the severity of allergic-type illnesses and decreasing the response to anti-inflammatory medications, such as steroids. [11][12][13][14][15][16][17][18] The relationship of obesity and in-hospital asthma outcomes is of particular interest because status asthmaticus is the most common reason for admission in children aged 3 to 12 years, accounting for approximately 150,000 admissions (7.4% of all hospitalizations for children and adolescents) and $835 million in hospital costs annually.…”
Section: Resultsmentioning
confidence: 99%
“…Previous pediatric burn literature is conflicting when look at the effect of BMI ! 85th percentile on in-patient morbidity and mortality [15,16,19,20]. Our study revealed that pediatric obesity was not a risk factor for skin grafting.…”
Section: Discussionmentioning
confidence: 46%
“…There are many confounding variable that may influence wound healing and grafting that were not accounted for in this study including presence of infection during hospitalization and/or nutritional factors. While previous pediatric burn literature detected an increased overall length of stay, intensive care days, and mechanical ventilator days for obese children [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], these outcomes were not looked at in this study as the majority of children included in our study suffered from minor or moderates burns which may limit the ability to generalize our results to more severely burned patients.…”
Section: Discussionmentioning
confidence: 67%
“…Such differences in response may be due to factors such as differences in body surface area, fat composition, reaction time and immunological response status. Regardless, studies that specifically discuss the mechanism of burns amongst overweight and obese paediatric patients as well as comparing and explaining differences in outcomes between obese adult and paediatric patients are lacking [34]. The management of the paediatric patient with burns can be different from that of an adult patient as well.…”
Section: Discussionmentioning
confidence: 97%